Some Commonly Used Words of Chepang - Adhikari, Rishiram (Saptagandaki Journal, 2017)
This paper presents some words of the Chepang language used in Chitwan district. The words collected in this paper were gathered from Shaktikhor VDC. Chepangs from various surroundings like Gorkha, Dhading, and Makawanpur have migrated and lived in Shaktikor in recent times so the words have been collected from the area. Collected words were gathered by asking questions to the participants who speak Chepang language in their daily life. The words were recorded before being presented in script by using roman script. Collected words are presented in two columns: Chepangs and English. The Saptagandaki Journal Vol.8 2017: 85-92